Tax incentives and the location of FDI: evidence from a panel of German multinationals - Thiess Buettner; Martin Ruf (Deutsche Bundesbank, 2005)
Using a firm-level dataset this paper investigates the impact of taxation on the decision of German multinationals to hold direct investments in other European countries or abroad. Controlling for firm-specific differences in the valuation of potential locations, the results confirm significant effects of tax incentives, market size, and of labor cost on cross-border location decisions. In accordance with Devereux and Griffith (1998) we find that the marginal tax rate has no predictive power for location decisions whereas effective average and statutory tax rates exert significant effects. In particular, the statutory tax rate has strong predictive power for the likelihood of direct investment holdings at a location. The results indicate that an increase in the statutory tax rate by 10 percentage points reduces the odds of observing some positive direct investment by approximately 20 %.
Keywords: H25; F23; F21; R38; 330; Location; FDI; Taxes; Firm-Level Panel Data; Fixed-Effects Logit Model; Direktinvestition; Multinationales Unternehmen; Standortwahl; Unternehmensbesteuerung; Steuerbelastung; Schätzung; Deutschland